Can Selected Functional Movement Screen Assessments Be Used to Identify Movement Deficiencies That Could Affect Multidirectional Speed and Jump Performance?. Issue 1 (January 2015) - Lockie, Robert G.; Schultz, Adrian B.; Jordan, Corrin A.; Callaghan, Samuel J.; Jeffriess, Matthew D.; Luczo, Tawni M.
Abstract : Abstract: Lockie, RG, Schultz, AB, Jordan, CA, Callaghan, SJ, Jeffriess, MD, and Luczo, TM. Can selected functional movement screen assessments be used to identify movement deficiencies that could affect multidirectional speed and jump performance? J Strength Cond Res 29(1): 195–205, 2015—The Functional Movement Screen (FMS) includes lower-body focused tests (deep squat [DS], hurdle step, in-line lunge) that could assist in identifying movement deficiencies affecting multidirectional sprinting and jumping, which are important qualities for team sports. However, the hypothesized relationship with athletic performance lacks supportive research. This study investigated relationships between the lower-body focused screens and overall FMS performance and multidirectional speed and jumping capabilities in team sport athletes. Twenty-two healthy men were assessed in the FMS, and multidirectional speed (0- to 5-m, 0- to 10-m, 0- to 20-m sprint intervals; 505 and between-leg turn differences, modified T-test and differences between initial movement to the left or right); and bilateral and unilateral multidirectional jumping (vertical [VJ], standing long [SLJ], and lateral jump) tests. Pearson's correlations ( r ) were used to calculate relationships between screening scores and performance tests ( p ⩽ 0.05). After the determination of any screens relating to athletic performance, subjects were stratified into groups (3 = high-performing group; 2 = intermediate-performing group; 1 = low-performing group) to investigate movement compensations. A 1-way analysis of variance ( p ⩽ 0.05) determined any between-group differences. There were few significant correlations. The DS did moderately correlate with between-leg 505 difference ( r = −0.423), and bilateral VJ ( r = −0.428) and SLJ ( r = −0.457). When stratified into groups according to DS score, high performers had a 13% greater SLJ when compared with intermediate performers, which was the only significant result. The FMS seems to have minimal capabilities for identifying movement deficiencies that could affect multidirectional speed and jumping in male team sport athletes.